Recent insertion/deletion (reINDEL) mutations: increasing awareness to boost molecular‐based research in ecology and evolution. Issue 1 (4th December 2014) - Schlick‐Steiner, Birgit C.; Arthofer, Wolfgang; Moder, Karl; Steiner, Florian M.
Abstract Today, the comparative analysis of DNA molecules mainly uses information inferred from nucleotide substitutions. Insertion/deletion (INDEL) mutations, in contrast, are largely considered uninformative and discarded, due to our lacking knowledge on their evolution. However, including rather than discarding INDELs would be relevant to any research area in ecology and evolution that uses molecular data. As a practical approach to better understanding INDEL evolution in general, we propose the study of recent INDEL (reINDEL) mutations – mutations where both ancestral and derived state are seen in the sample. The precondition for reINDEL identification is knowledge about the pedigree of the individuals sampled. Sound reINDEL knowledge will allow the improved modeling needed for including INDELs in the downstream analysis of molecular data. Both microsatellites, currently still the predominant marker system in the analysis of populations, and sequences generated by next‐generation sequencing, a promising and rapidly developing range of technologies, offer the opportunity for reINDEL identification. However, a 2013 sample of animal microsatellite studies contained unexpectedly few reINDELs identified. As most likely explanation, we hypothesize that reINDELs are underreported rather than absent and that this underreporting stems from common reINDEL unawareness. If our hypothesis applies, increased reINDEL awareness should allow gathering data rapidly. We recommend the routine reporting of either the absence or presence of reINDELs together with standardized key information on the nature of mutations when they are detected and the use of the keyword "reINDEL" to increase visibility in both instances of successful and unsuccessful search.